1997
DOI: 10.1074/jbc.272.14.9300
|View full text |Cite
|
Sign up to set email alerts
|

Two Restricted Sites on the Surface of the Nerve Growth Factor Molecule Independently Determine Specific TrkA Receptor Binding and Activation

Abstract: Nerve growth factor (NGF) and neurotrophin-3 (NT-3) mediate activities such as survival, differentiation, and proliferation in various subsets of neurons. In this report, we define precisely the residues in human NGF responsible for NGF biological activity and binding specificity to the neurotrophin receptor TrkA. In earlier studies we defined five amino acid residues of NGF which confer NGF-like activity to NT-3 when replacing corresponding residues in the 120-amino acid long NT-3 molecule. Using this gain-of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 54 publications
2
32
0
Order By: Relevance
“…However, a chimeric molecule that additionally replaced residues 3-9 of the N-terminus reduced TrkA binding, activation, and biological activity to <1% (Ibanez et al, 1993). Other substitution and deletion studies confirmed the importance of the N-terminus in specificity (Kullander et al, 1997;Woo et al, 1995;Kahle et al, 1992;Shih et al, 1994). Data from the crystal structure of human recombinant NGF complexed with the TrkA-d5 domains showed that the amino terminal residues 6-9, which were not well-defined in the original NGF crystal structure, adopted a helical conformation upon complex formation with their side chains almost completely buried in the interface (McDonald et al, 1991;Wiesmann et al, 1999) (Fig.…”
Section: The Specificity Patchmentioning
confidence: 82%
See 4 more Smart Citations
“…However, a chimeric molecule that additionally replaced residues 3-9 of the N-terminus reduced TrkA binding, activation, and biological activity to <1% (Ibanez et al, 1993). Other substitution and deletion studies confirmed the importance of the N-terminus in specificity (Kullander et al, 1997;Woo et al, 1995;Kahle et al, 1992;Shih et al, 1994). Data from the crystal structure of human recombinant NGF complexed with the TrkA-d5 domains showed that the amino terminal residues 6-9, which were not well-defined in the original NGF crystal structure, adopted a helical conformation upon complex formation with their side chains almost completely buried in the interface (McDonald et al, 1991;Wiesmann et al, 1999) (Fig.…”
Section: The Specificity Patchmentioning
confidence: 82%
“…Scott et al, 1983;Walsh et al, 1999;Wiesmann et al, 1999;Yeo et al, 1997) . Sequence alignments of NGF, BDNF, and NT-3 (Ibanez et al, 1992;Ibanez et al, 1991;Ibanez et al, 1993;Ilag et al, 1994;Kullander & Ebendal, 1994;Kullander et al, 1997) demonstrate that each neurotrophin possesses seven variable regions that include the same residue positions. These are the N-terminus (residues 1-9), variable region I ( -hairpin loop 1, residues 23-35), variable region II ( -hairpin loop 2, residues 40-49), variable region III ( -reverse turn loop 3, residues 59-66), variable region IV ( -strand, residues 79-88), variable region V ( -hairpin loop 4, residues 95-99), and the C-terminus (residues 111-118) (Fig.…”
Section: Molecular Analysis Of Neurotrophin Structure and Rationale Omentioning
confidence: 99%
See 3 more Smart Citations